A case of renal cell carcinoma in a patient with situs inversus: Operative considerations and a review of the literature - Oake, Justin; Drachenberg, Darrel (Canadian Urological Association Journal, 2017)
Situs inversus, an uncommon mirror-image reversal of the major visceral and thoracic organs, is seldom of medical significance. However, the recognition of their unique anatomy is extremely important for those requiring surgical intervention. There are very few reported cases of renal cell carcinoma (RCC) developing in people with situs inversus. To our knowledge, this is the first reported case in Canada. A review of the literature only identified nine published cases worldwide. Here, we review and summarize pertinent information, including patient age and sex, size and location of tumour, method of surgery, and pathology. Our case, a 65-yearold male, presented with left flank pain and gross hematuria. He was diagnosed with left renal cancer as well as tumour thrombus extending into the left renal veins and inferior vena cava (IVC), clinical T3aN0M0. An abdomen and pelvis computed tomography (CT) scan showed a left-to-right reversal of his organs, a mirrorimage, and situs inversus was diagnosed. A left radical nephrectomy with left renal vein and IVC tumour thrombectomy through a left open midline incision was performed.